Inhibition of stromal MAOA leading activation of WNT5A enhance prostate cancer immunotherapy by involving the transition of cancer-associated fibroblasts - Hui Li; Mengyao Li; Lijun Yang; Tong Lu; Zhite Zhao; Yaohua Hu; Xinglin He; Yifan Ma; Minli Huang; Changhong Shi (Journal for ImmunoTherapy of Cancer)
Background The interaction between stromal cells and the tumor immune microenvironment (TIME) is acknowledged as a critical driver in the progression of prostate cancer (PCa). Monoamine oxidase A (MAOA), a mitochondrial enzyme that catalyzes the degradation of monoamine neurotransmitters and dietary amines, has been linked to the promotion of prostate tumorigenesis, particularly when upregulated in stromal cells. However, the detailed mechanisms of MAOA’s interaction with TIME have not been fully elucidated.Methods We reanalyzed a single-cell sequencing dataset to evaluate the role of MAOA in the stroma, verify the impact of stromal MAOA alterations on CD8+ T cell responses by co-culturing stromal cells and immune cells in vitro. Furthermore, C57BL/6J mouse subcutaneous transplant tumor models and dual humanized mouse models were established to investigate the function of MAOA in vivo and the potential of its inhibitors for immunotherapy.Results Our study demonstrates that inhibiting MAOA in stromal cells facilitates the conversion of myofibroblastic cancer-associated fibroblasts (myCAFs), thereby improving the immunosuppressive environment of PCa. The strategic combination of MAOA inhibition with immune checkpoint inhibitors elicits a synergistic antitumor effect. Specifically, MAOA inhibition in stromal cells leads to increased production of WNT5A, which subsequently activates the cytotoxic capacity of CD8+ T cells through the Ca2+-NFATC1 signaling pathway.Conclusions Our findings highlight the critical role of MAOA in modulating cancer-associated fibroblasts within the PCa immune microenvironment, presenting a novel therapeutic strategy to augment the efficacy of immunotherapy for PCa.